From the Laboratory to the Field: Updating Capacity Building in Medical Entomology. Issue 9 (September 2017) - Almeida, Antonio Paulo Gouveia; Fouque, Florence; Launois, Pascal; Sousa, Carla A.; Silveira, Henrique
Abstract : Training and innovation in the field of medical entomology are essential to mitigate the burden of vector-borne diseases globally. However, there is a shortage of medical entomologists worldwide, and there are large discrepancies in capacity building in this field. In this article, we discuss the current situation, what is needed from the medical entomologist of today, and how we can bridge this gap.